Progress in Nanophotonics 1 - Ohtsu, Motoichi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book focuses on the recent progress in nanophotonics technology to be used to develop novel nano-optical devices, fabrication technology, and security systems. It begins with a review of the concept of dressed photons and applications to devices, fabrication, and systems; principles and applications. Further topics include: DNA process for quantum dot chain, photon enhanced emission microscopy, near field spectroscopy of metallic nanostructure, self-organized fabrication of composite semiconductor quantum dots, formation of metallic nanostructure, and nanophotonic information systems with security. These topics are reviewed by seven leading scientists. This overview is a variable resource for engineers and scientists working in the field of nanophotonics.
Nanophotonics: Dressed photon technology for qualitatively innovative optical devices, fabrication, and systems -- DNA process for quantum dot chain -- Photon enhanced emission microscopy -- Nearfield spectroscopy of metallic nanostructure -- Self-organized fabrication of composite semiconductor quantum dots -- Metallic nanostructure -- Nanophotonic information systems with security.
Keywords: Physics; Microwaves; Physics; Atomic, Molecular, Optical and Plasma Physics; Laser Technology, Photonics; Nanoscale Science and Technology; Applied and Technical Physics; Microwaves, RF and Optical Engineering